An Observational Study On Health Issue Developed During Lockdown W.S.R. Physical Fitness Challenges - Saini, Urmila Kumari; Mishra, Pramod Kumar; Sharma, Indumati; Parashar, Rahul; Kumar, Mahesh; Gourana, Payal (International Research Journal of Ayurveda & Yoga, 2021)
The new virus is a global threat produced by a novel corona virus that was initially discovered in December 2019 near a seafood market in Wuhan, Hubei, China. Severe Acute Respiratory Syndrome –Corona Virus (SARS-CoV2), also known as novel Coronavirus, is a new virus that causes fever, chills, cough, coryza, sore throat, breathing trouble, myalgia, nausea, vomiting, and diarrhoea (2019- nCoV). The incubation period is predicted to be 5.2 days on average. There were no medicines or vaccines available, and the populace had no immunity to begin with.